Pengaruh Likuiditas, Leverage Dan Profitabilitas Terhadap Tax Avoidance Pada Perusahaan Food And Beverage Di BEI Tahun 2019-2021 - Sari Wahyu Utami; Siti Alliyah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims to determine the effect of Liquidity, Leverage, and Profitability on Tax Avoidance in Food and Beverage Companies Listed on the IDX for the 2019-2021 period. Documentation data collection method while the type of data is secondary data. The sample selection used purposive sampling method. The number of research samples is 20 samples. Data analysis used to test the hypothesis is by using multiple linear regression analysis techniques. Tested using the SPSS 26 application. Based on the results of the study it showed that (1) Current Ratio (CR) has a significant positive effect on tax avoidance, (2) Debt to Assets Ratio (DAR) has a significant positive effect on tax avoidance, (3) Return on Assets (ROA) has no significant positive effect on tax avoidance.